2023
DOI: 10.1021/acsami.3c04848
|View full text |Cite
|
Sign up to set email alerts
|

Unique Contact Point Modification Technique for Boosting the Performance of a Triboelectric Nanogenerator and Its Application in Road Safety Sensing and Detection

Abstract: A triboelectric nanogenerator (TENG) is a potential technique that can convert waste kinetic energy to electrical energy by contact separation followed by electrostatic induction. Herein, a unique contact point modification technique has been reviewed carefully via the enlargement of the effective surface area of the tribo layer by using a simple and scalable printing method. In this study, the zinc sulfide (ZnS) nanostructure morphology has been introduced directly on an aluminum electrode (Al) as a tribo pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…It was observed that changing the interconnection direction solely affected the polarity of the voltage and current while leaving their magnitudes unaffected. This finding underscores the independence of the output voltage and current from the interconnection direction, which aligns with earlier research findings [35]. The performance of the TENG primarily depends on the spacing between the friction layers, the dielectric constant, the design structure, the friction frequency, and other relevant factors.…”
Section: Resultssupporting
confidence: 89%
“…It was observed that changing the interconnection direction solely affected the polarity of the voltage and current while leaving their magnitudes unaffected. This finding underscores the independence of the output voltage and current from the interconnection direction, which aligns with earlier research findings [35]. The performance of the TENG primarily depends on the spacing between the friction layers, the dielectric constant, the design structure, the friction frequency, and other relevant factors.…”
Section: Resultssupporting
confidence: 89%
“…TENGs operate on the combined effect of contact electrification and electrostatic induction, and this process can occur between two materials. As a result, multiple research groups have investigated various materials, including polymers, fabrics, self-assembled materials, metal oxides, metals, sulfides, metal–organic frameworks, covalent organic frames works, graphene, and MXene materials, to improve the power density of TENGs. The power density of the TENG is mainly enhanced by (a) careful selection of frictional layer (materials) with a significant difference in their work function and (b) physical and chemical surface modification of frictional layers. The literature review of different materials-based TENGs and their performance is presented in Supporting Information Table S2.…”
Section: Introductionmentioning
confidence: 99%